2018
DOI: 10.1038/s41598-018-23904-3
|View full text |Cite
|
Sign up to set email alerts
|

Health status in subjects with suspected obstructive sleep apnea and comparison with a general population

Abstract: The purpose of this study was to assess health status (HS) in patients with clinical suspicion of obstructive sleep apnea (OSA) in order to estimate the dose response relationship between HS and OSA severity, and to compare HS in this clinical cohort with a general population sample (N = 5000). Patients referred to an overnight sleep study due to suspected OSA, whom also responded to the SF-36 questionnaire, were included (N = 418). Of these, 194 showed normal findings, while 111, 60 and 53 demonstrated mild, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…It was also determined that this relation was negative with SF-36 sub-dimensions, and positive with other scales. These findings are consistent with the results of the previous studies reporting that sleep problems of the OSAS patients affect mental and social functioning as well as physical health in a negative way [35][36][37][38][39]. It was considered that there is an agreement between the MOS sleep scale result and the scales that were applied simultaneously.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was also determined that this relation was negative with SF-36 sub-dimensions, and positive with other scales. These findings are consistent with the results of the previous studies reporting that sleep problems of the OSAS patients affect mental and social functioning as well as physical health in a negative way [35][36][37][38][39]. It was considered that there is an agreement between the MOS sleep scale result and the scales that were applied simultaneously.…”
Section: Discussionsupporting
confidence: 91%
“…In previous years, the relations between OSAS and neuropsychological and functional deficiencies including daytime sleepiness, impaired sleep quality, fatigue, anxiety, depression and reduced quality of life have been shown [34,35]. For this reason, the MOS-sleep scale and PSQI, CIS, BDI, BAI, ESS, SHI and SF-36 scales were applied simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with other studies concerning the EORTC QLQ c30 questionnaire, although the reported absolute numbers are higher in this study [29,30]. Regarding SF 36 similar results have been reported for a general OSA population [31].…”
Section: Comparison With the Existing Literaturesupporting
confidence: 93%
“…Nasal CPAP improves the QoL in OSA patients, including an improvement in depression . Most of these studies demonstrated the clinical effectiveness of nCPAP in terms of EDS, QOL and cardiovascular complications .…”
Section: Discussionmentioning
confidence: 97%
“…Nasal CPAP improves the QoL in OSA patients, including an improvement in depression. 23 Most of these studies demonstrated the clinical effectiveness of nCPAP in terms of EDS, QOL and cardiovascular complications. 24 Nasal CPAP treatment has supported significant improvement in the depressive symptoms of OSA patients due to its reduction of daytime sleepiness.…”
Section: Discussionmentioning
confidence: 99%